An EGCG nanocomposition with strong antioxidant and anti-photoaging effects, and preparation method and application thereof

Through a two-step functionalized phospholipid self-assembly wrapping method, EGCG nanocomposition was prepared, which solved the stability and transdermal absorption of EGCG in cosmetics, and achieved efficient antioxidant and anti-photoaging effects.

CN118892425BActive Publication Date: 2025-03-14GUANGZHOU ZHONGZHUANG BEAUTY COSMETICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410920897.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2025-03-14
Estimated Expiration
2044-07-10

AI Technical Summary

Technical Problem

When EGCG is used in cosmetics, there are problems such as poor stability, easy color change, and low transdermal absorption utilization. The prior art EGCG nanoparticles encapsulation rate is low and may cause irritation to the skin.

Method used

Using a two-step functionalized phospholipid self-assembly wrapping method, a nanocomposition precursor is prepared first to wrap EGCG, and then EGCG is self-assembly protected by phospholipid self-assembly to form an EGCG nanocomposition. This method improves the stability and skin permeability of EGCG by adjusting the composition and structure of the phospholipid membrane.

Benefits of technology

It improves the stability, encapsulation rate, antioxidant effect and skin permeability of EGCG, enhances its anti-photoaging and protein carbonylation inhibition effects, and its effect is better than that of EGCG aqueous solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118892425B_ABST
    Figure CN118892425B_ABST
Patent Text Reader

Abstract

The present invention discloses an EGCG nanocomposition with strong antioxidant and anti-photoaging effects, and a preparation method and application thereof. The EGCG nanocomposition is formed by encapsulating the functional active substance EGCG through two-step functionalized phospholipid self-assembly, firstly preparing a nanocomposition precursor to encapsulate EGCG, then self-assembling and protecting the nanocomposition precursor through phospholipids, and simultaneously using two membrane material stabilizers of different properties to compound and regulate the phospholipid membrane to obtain the EGCG nanocomposition. The EGCG nanocomposition of the present invention has good stability, encapsulation rate, antioxidant effect, sustained release performance and skin permeability. The EGCG nanocomposition of the present invention also has excellent DNA damage repair effect and protein carbonylation inhibition effect, and can be used in skin topical preparations to play an antioxidant, anti-photoaging and skin yellowing effect, and its efficacy is better than that of EGCG aqueous solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano-carrier materials, and in particular relates to an EGCG nano-composition with strong anti-oxidation and anti-photoaging effects, and a preparation method and application thereof. Background Art

[0002] The skin is the largest organ on the human body surface and is in direct contact with the external environment. When the skin is exposed to harmful stimuli such as air pollution, oxidation, and ultraviolet radiation for a long time, skin aging is likely to occur. Skin aging is mainly manifested in dry skin, sagging, wrinkles, pigmentation, etc. Therefore, "anti-aging" has always been a hot topic of concern. Among them, dark yellow skin is mainly caused by the accumulation of carbonylated proteins in the skin. Therefore, protein carbonylation inhibition can effectively improve the problem of dark yellow skin.

[0003] Epigallocatechin gallate (EGCG) is a catechin compound and the component with the highest content in catechins, accounting for 50-60%. EGCG has a special stereochemical structure, and it has very strong antioxidant activity. Its ability to scavenge active free radicals is significantly higher than that of vitamin C and vitamin E, and it can protect cells and DNA from damage, thereby delaying skin aging. However, when EGCG is actually used as an anti-aging additive in cosmetics, there are problems such as poor stability, easy color change, and low transdermal absorption utilization. For example, cosmetic products containing EGCG are prone to discoloration under photothermal conditions. This is because the EGCG molecular structure is rich in phenolic hydroxyl groups. Under photothermal conditions, phenolic hydroxyl groups are easily oxidized to form quinone substances, which eventually cause the product to turn red and the anti-aging effect is weakened. Secondly, due to its good water solubility, EGCG has low transdermal absorption utilization and cannot effectively penetrate the stratum corneum of the skin, with a transmittance of only 0.44% (Drug Delivery, 2017, 24: 61-74).

[0004] In order to improve the stability and transdermal permeability of EGCG, EGCG is often encapsulated in the prior art. Liu Chunhua (South China Agricultural University, 2020) used sodium caseinate and gum arabic as nanocarrier wall materials to encapsulate EGCG to prepare an EGCG nanoparticle, and studied its antioxidant application in gastric juice and intestinal juice, but the EGCG nanoparticle encapsulation rate of this technology was low, only 62.8%. Liu Hong (Zhejiang Gongshang University, 2015) used ultrasound to prepare an EGCG nano-alcohol body for anti-ultraviolet radiation enhancement; Sun Xiang (Jiangnan University, 2019) used ethanol injection to prepare an EGCG liposome. Both of the above existing methods use anhydrous ethanol as a solvent, which is easy to irritate the skin when applied to the skin. Therefore, the existing technology for EGCG encapsulation treatment often has problems such as low encapsulation rate and high irritation. In addition, most of the existing technologies for EGCG encapsulated products only explore their physical and chemical properties (such as particle size, encapsulation rate, etc.) and basic research on anti-cancer, and there has been no report on the application research of EGCG inclusion-related products in improving skin photoaging and skin yellowing. Summary of the invention

[0005] In order to overcome the above-mentioned prior art, the primary purpose of the present invention is to provide a method for preparing an EGCG nanocomposition with strong antioxidant, anti-photoaging and protein carbonylation inhibitory effects.

[0006] Another object of the present invention is to provide an EGCG nanocomposition prepared by the above method, which has strong antioxidant, anti-photoaging and protein carbonylation inhibition effects.

[0007] The present invention also provides the application of the EGCG nano-composition prepared by the above method and having strong anti-oxidation, anti-photoaging and protein carbonylation inhibition effects.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] The EGCG nanocomposition of the present invention is formed by two-step functional phospholipid self-assembly encapsulating the efficacy active substance EGCG, including a first step of nanocomposition precursor preparation process and a second step of dual phospholipid nanocomposition preparation process.

[0010] A method for preparing an EGCG nanocomposition with strong antioxidant and anti-photoaging effects comprises the following steps:

[0011] (1) Preparation of nanocomposite precursor:

[0012] The phospholipid and EGCG are added to an organic solvent and stirred evenly to obtain an organic phase; the polyol is added to water and stirred evenly to obtain an aqueous phase; the organic phase is uniformly added dropwise to the aqueous phase, and after the addition is completed, the stirring is continued to obtain a mixed solution; the organic solvent is removed from the obtained mixed solution; and the mixed solution is dried to obtain a nanocomposite precursor;

[0013] The phospholipid content in the mixed solution is 1%-10% by mass percentage;

[0014] (2) Preparation of dual phospholipid nanocomposite:

[0015] The phospholipid, rigid membrane material stabilizer and flexible membrane material stabilizer are added to the polyol, and stirred evenly to obtain an alcohol phase; the nanocomposite precursor is added to water, and stirred and dispersed evenly to obtain an aqueous phase; the aqueous phase is uniformly added to the alcohol phase, and after the addition is completed, the stirring is continued to obtain a mixed solution; the mixed solution is subjected to nano-processing to obtain an EGCG nanocomposite, wherein the mass percentage of EGCG in the EGCG nanocomposite is 0.6%-6.0%;

[0016] In terms of mass percentage, the phospholipid content in the mixed solution is 0.1%-1.0%, the rigid membrane material stabilizer content is 0.1%-0.3%, and the flexible membrane material stabilizer content is 0.5%-2.0%;

[0017] The molecular structure of the rigid film material stabilizer contains a polycyclic structural unit or a benzene ring structural unit; the molecular structure of the flexible film material stabilizer is a straight chain type or a straight chain compound.

[0018] Preferably, the rigid film material stabilizer includes one or more of cholesterol, phytosterol, sodium cholate, vitamin D, resorcinol, phenylalanine, and phenylpropanol.

[0019] Preferably, the flexible film material stabilizer includes one or more of caprylic / capric triglyceride, caprylic / capric / linoleic triglyceride, caprylic / capric / lauric triglyceride, oleic acid, linoleic acid, octyldodecanol, and octyldodecanol oleate.

[0020] Preferably, the mass percentage of EGCG in the EGCG nanocomposition is 3±2%.

[0021] Preferably, in terms of mass percentage, the mixed solution in step (1) contains 5±2% phospholipids, 10%-20% EGCG, 1%-10% polyol, 10%-50% organic solvent, and 13%-78% water.

[0022] Preferably, in terms of mass percentage, the mixed solution in step (2) contains 0.3±0.2% phospholipid, 0.15±0.05% rigid membrane material stabilizer, 1.5%±0.5% flexible membrane material stabilizer, 5%-50% polyol, 1.0%-10% nanocomposite precursor, and 37.3%-88.4% water.

[0023] Preferably, the phospholipid in step (1) is at least one of soybean lecithin, hydrogenated soybean lecithin, enzymatic lecithin, dipalmitoylphosphatidylcholine, palmitoylphosphatidylglycerol and egg yolk lecithin.

[0024] Preferably, the phospholipid in step (2) is at least one of soybean lecithin, hydrogenated soybean lecithin, dipalmitoylphosphatidylcholine, palmitoylphosphatidylglycerol and egg yolk lecithin.

[0025] Preferably, the organic solvent in step (1) is one or more of anhydrous ethanol, methanol, dichloromethane, chloroform, acetone, tetrahydrofuran, n-hexane, petroleum ether, and ethyl acetate.

[0026] Preferably, the polyol in step (1) is a sugar alcohol, which is one or more of maltitol, D-sorbitol, xylitol, erythritol, mannitol and lactitol.

[0027] Preferably, the polyol in step (2) is at least one of glycerol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,2-hexanediol, ethoxydiglycol, dipropylene glycol, and polyethylene glycol (Mn=400).

[0028] Preferably, the first two stirring conditions of step (1) are as follows: stirring speed of 100-800 rpm; stirring temperature of 30-80°C; stirring time of 20-60 min; dropping speed of 1-10 ml / min; the third stirring conditions are as follows: stirring speed of 100-800 rpm; stirring temperature of 30-80°C; stirring time of 10-30 min; the organic solvent is removed from the obtained mixed solution by rotary evaporation, the rotary evaporation speed is 100-350 rpm; the rotary evaporation temperature is 30-80°C; the rotary evaporation time is 1-3 h. The drying method can be freeze drying, vacuum drying, and air drying, preferably freeze drying; the drying time is 24-72 h.

[0029] Preferably, the stirring conditions for the first two times of step (2) are: stirring speed of 100-800 rpm; stirring temperature of 10-50°C; stirring time of 20-60 min; and dropwise addition rate of 1-10 mL / min; and the stirring conditions for the third time are: stirring speed of 100-800 rpm; stirring temperature of 10-50°C; and stirring time of 10-30 min.

[0030] Preferably, the nano-processing described in step (2) includes high-speed shear dispersion processing and / or microfluidization homogenization processing; the rotation speed of the high-speed shear dispersion processing is 6000-12000rpm, and the shear dispersion time is 10-30min; the homogenization pressure of the microfluidization homogenization processing is 50-120MPa, and the number of homogenization cycles is 2-6 times.

[0031] The stirring method in steps (1) and (2) is mechanical stirring or magnetic stirring.

[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0033] (1) The present invention adopts a two-step functionalized phospholipid self-assembly method to encapsulate the active ingredient EGCG, first preparing a nanocomposite precursor to encapsulate EGCG, and then self-assembling and protecting the nanocomposite precursor with phospholipids to obtain an EGCG nanocomposite. The EGCG nanocomposite of the present invention has good stability, encapsulation rate, antioxidant effect, sustained release performance and skin permeability.

[0034] (2) The present invention uses two membrane material stabilizers with different properties to compound and regulate the phospholipid membrane, and the obtained EGCG nanocomposite has better stability, encapsulation rate, antioxidant effect and skin permeability.

[0035] (3) The EGCG nanocomposition of the present invention also has excellent DNA damage repair effect and protein carbonylation inhibition effect. It can play an antioxidant, anti-photoaging and skin yellowing effect when used in skin topical preparations, and its efficacy is better than that of EGCG aqueous solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a diagram showing the results of DNA damage repair using the γ-H2AX method of the present invention.

[0037] Figure 2 This is a graph showing the results of the protein carbonylation inhibition experiment of the present invention. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. If the specific conditions are not specified in the examples, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not indicated for the reagents or instruments used, they are all conventional products that can be purchased commercially. The reagents used in the examples can be purchased conventionally from the market unless otherwise specified.

[0039] In the embodiments of the present invention, the EGCG (purity 98%), maltitol (purity 98%), D-sorbitol (purity 98%), and xylitol (purity 98%) used can be purchased directly from Shanghai Aladdin Biotechnology Co., Ltd.

[0040] Example 1

[0041] (1) Preparation of nanocomposite precursor: 5.0% soybean lecithin and 15% EGCG were added to 30% anhydrous ethanol at 60°C, and stirred at 300 rpm for 30 min until the above raw materials were fully dissolved to obtain an organic phase. 5% maltitol was added to 45% deionized water at 60°C, and stirred at 300 rpm for 30 min until the above raw materials were fully dissolved to obtain an aqueous phase. While maintaining the temperature at 60°C, the organic phase was uniformly added dropwise to the aqueous phase at a drop speed of 3 ml / min. After the dropwise addition was completed, the mixture was stirred at 60°C for 15 min (at a speed of 300 rpm) to obtain a mixed solution. The obtained mixed solution was subjected to rotary evaporation to remove anhydrous ethanol at a rotary evaporation speed of 150 rpm, a rotary evaporation temperature of 40°C, and a rotary evaporation time of 2 h. After freeze drying for 48 h, a nanocomposite precursor was obtained. In the nanocomposite precursor, calculated by mass percentage, phospholipid: EGCG: maltitol = 20%: 60%: 20%.

[0042] (2) Preparation of EGCG nanocomposite: 0.3% by mass of hydrogenated lecithin, 0.15% of cholesterol, and 1.5% of caprylic / capric triglyceride were added to a mixed solution of 25% by mass of glycerol and 10% by mass of 1,2-hexanediol, and stirred at 30°C (speed of 300 rpm) for 30 min until the above raw materials were fully dissolved to obtain an alcohol phase. 5% by mass of the nanocomposite precursor was added to 58.05% by mass of deionized water, and stirred at 30°C (speed of 300 rpm) for 30 min until the nanocomposite precursor was uniformly dispersed to obtain an aqueous phase. While maintaining the temperature at 30°C, the aqueous phase was uniformly added dropwise to the alcohol phase at a dropwise speed of 3 ml / min. After the addition was completed, stirring was continued at 30°C (speed of 300 rpm) for 15 min to obtain a mixed solution. The mixed solution was dispersed by high-speed shearing (10000 rpm) for 20 min; and then subjected to high-pressure microfluidization homogenization treatment with a homogenization pressure of 80 MPa and a homogenization number of 4 times to obtain an EGCG nanocomposite.

[0043] In Example 1 of the present invention, the proportion of the active ingredient EGCG in the EGCG nanocomposition is 3%. Example 2 (Examples 2-5, the amount of phospholipid added in the nanocomposition precursor is different)

[0044] (1) Preparation of nanocomposite precursor: The 5% by mass percent soybean lecithin in Example 1 was replaced with 1% by mass percent soybean lecithin, and the 45% by mass percent deionized water was replaced with 49% by mass percent deionized water, and the rest remained unchanged to prepare a nanocomposite precursor. In the nanocomposite precursor of this example, by mass percentage, phospholipid: EGCG: maltitol = 4.8%: 71.4%: 23.8%.

[0045] (2) Preparation of EGCG nanocomposite: The EGCG nanocomposite was prepared by replacing the 5% by mass of the nanocomposite precursor in Example 1 with 4.2% by mass of the nanocomposite precursor prepared above, while keeping the rest unchanged.

[0046] In Example 2 of the present invention, the proportion of the active ingredient EGCG in the EGCG nanocomposition remains the same as that in Example 1, which is 3%.

[0047] Example 3

[0048] (1) Preparation of nanocomposite precursor: The 5% by mass percent soybean lecithin in Example 1 was replaced with 3% by mass percent soybean lecithin, and the 45% by mass percent deionized water was replaced with 47% by mass percent deionized water, and the rest remained unchanged to prepare a nanocomposite precursor. In the nanocomposite precursor of this example, by mass percentage, phospholipid: EGCG: maltitol = 13%: 65.2%: 21.8%.

[0049] (2) Preparation of EGCG nanocomposite: The EGCG nanocomposite was prepared by replacing the 5% by mass of the nanocomposite precursor in Example 1 with 4.6% by mass of the nanocomposite precursor prepared above, while keeping the rest unchanged.

[0050] In Example 3 of the present invention, the proportion of the active ingredient EGCG in the EGCG nanocomposition remains the same as that in Example 1, which is 3%.

[0051] Example 4

[0052] (1) Preparation of nanocomposite precursor: The 5% by mass percent soybean lecithin in Example 1 was replaced with 7% by mass percent soybean lecithin, and the 45% by mass percent deionized water was replaced with 43% by mass percent deionized water, and the rest remained unchanged to prepare a nanocomposite precursor. In the nanocomposite precursor of this embodiment, by mass percentage, phospholipid: EGCG: maltitol = 25.9%: 55.6%: 18.5%.

[0053] (2) Preparation of EGCG nanocomposite: The EGCG nanocomposite was prepared by replacing the 5% by mass percentage of the nanocomposite precursor in Example 1 with 5.4% by mass percentage of the nanocomposite precursor prepared above, while keeping the rest unchanged.

[0054] In Example 4 of the present invention, the proportion of the active ingredient EGCG in the EGCG nanocomposition remains the same as that in Example 1, which is 3%.

[0055] Example 5

[0056] (1) Preparation of nanocomposite precursor: The 5% by mass percent soybean lecithin in Example 1 was replaced with 10% by mass percent soybean lecithin, and the 45% by mass percent deionized water was replaced with 40% by mass percent deionized water, and the rest remained unchanged to prepare a nanocomposite precursor. In the nanocomposite precursor of this example, by mass percentage, phospholipid: EGCG: maltitol = 33.3%: 50%: 16.7%.

[0057] (2) Preparation of EGCG nanocomposite: The EGCG nanocomposite was prepared by replacing 5% by mass of the nanocomposite precursor in Example 1 with 6% by mass of the nanocomposite precursor prepared above, while keeping the rest unchanged.

[0058] In Example 3 of the present invention, the proportion of the active ingredient EGCG in the EGCG nanocomposition remains the same as that in Example 1, which is 3%.

[0059] Example 6 (Examples 6-9, different amounts of hydrogenated lecithin added)

[0060] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0061] (2) The 0.3% by mass percentage of hydrogenated lecithin in Example 1 was replaced with 0.1% by mass percentage of hydrogenated lecithin, and the 60.05% by mass percentage of deionized water was replaced with 60.25% by mass percentage of deionized water, and the rest remained unchanged, so that the total mass percentage was 100%. The subsequent treatment method remained unchanged to prepare the EGCG nanocomposite.

[0062] In Example 6 of the present invention, the proportion of the active ingredient EGCG in the EGCG nanocomposition is 3%.

[0063] Example 7

[0064] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0065] (2) The 0.3% by mass percent hydrogenated lecithin in Example 1 was replaced with 0.5% by mass percent hydrogenated lecithin, and the 60.05% by mass percent deionized water was replaced with 59.85% by mass percent deionized water, and the rest remained unchanged, so that the total mass percentage was 100%. The subsequent treatment method remained unchanged to prepare the EGCG nanocomposite.

[0066] In Example 7 of the present invention, the proportion of the active ingredient EGCG in the EGCG nanocomposition is 3%.

[0067] Example 8

[0068] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0069] (2) The 0.3% by mass percentage of hydrogenated lecithin in Example 1 was replaced with 0.7% by mass percentage of hydrogenated lecithin, and the 60.05% by mass percentage of deionized water was replaced with 59.65% by mass percentage of deionized water, and the rest remained unchanged, so that the total mass percentage was 100%. The subsequent treatment method remained unchanged to prepare the EGCG nanocomposite.

[0070] In Example 8 of the present invention, the active ingredient EGCG accounts for 3% of the EGCG nanocomposition.

[0071] Example 9

[0072] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0073] (2) The 0.3% by mass percentage of hydrogenated lecithin in Example 1 was replaced with 1.0% by mass percentage of hydrogenated lecithin, and the 60.05% by mass percentage of deionized water was replaced with 59.35% by mass percentage of deionized water, and the rest remained unchanged, so that the total mass percentage was 100%. The subsequent treatment method remained unchanged to prepare the EGCG nanocomposite.

[0074] In Example 9 of the present invention, the proportion of the functional active ingredient EGCG in the EGCG nanocomposition is 3%.

[0075] Example 10 (Examples 10-12 have different rigid stabilizer types)

[0076] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0077] (2) The EGCG nanocomposite was prepared by replacing 0.15% by mass of cholesterol in Example 1 with 0.15% by mass of sodium cholate, while keeping the rest unchanged.

[0078] In Example 10 of the present invention, the active ingredient EGCG accounts for 3% of the EGCG nanocomposition.

[0079] Embodiment 11

[0080] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0081] (2) The EGCG nanocomposite was prepared by replacing 0.15% by mass of cholesterol in Example 1 with 0.15% by mass of resorcinol, while keeping the rest unchanged.

[0082] In Example 11 of the present invention, the proportion of the active ingredient EGCG in the EGCG nanocomposition is 3%.

[0083] Example 12

[0084] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0085] (2) The EGCG nanocomposite was prepared by replacing 0.15% by mass of cholesterol in Example 1 with 0.15% by mass of phenylalanine, while keeping the rest unchanged.

[0086] In Example 12 of the present invention, the active ingredient EGCG accounts for 3% of the EGCG nanocomposition.

[0087] Example 13 (Examples 13-15 have different amounts of rigid stabilizer added)

[0088] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0089] (2) The cholesterol with a mass percentage of 0.15% in Example 1 was replaced with the cholesterol with a mass percentage of 0.1%, and the deionized water with a mass percentage of 60.05% was replaced with the deionized water with a mass percentage of 60.10%, and the rest remained unchanged, so that the total mass percentage was 100%. The subsequent treatment method remained unchanged to prepare the EGCG nanocomposite.

[0090] In Example 13 of the present invention, the active ingredient EGCG accounts for 3% of the EGCG nanocomposition.

[0091] Embodiment 14

[0092] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0093] (2) The cholesterol with a mass percentage of 0.15% in Example 1 was replaced with the cholesterol with a mass percentage of 0.2%, and the deionized water with a mass percentage of 60.05% was replaced with the deionized water with a mass percentage of 60.00%, and the rest remained unchanged, so that the total mass percentage was 100%. The subsequent treatment method remained unchanged to prepare the EGCG nanocomposite.

[0094] In Example 14 of the present invention, the active ingredient EGCG accounts for 3% of the EGCG nanocomposition.

[0095] Embodiment 15

[0096] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0097] (2) The cholesterol with a mass percentage of 0.15% in Example 1 was replaced with the cholesterol with a mass percentage of 0.3%, and the deionized water with a mass percentage of 60.05% was replaced with the deionized water with a mass percentage of 59.90%, and the rest remained unchanged, so that the total mass percentage was 100%. The subsequent treatment method remained unchanged to prepare the EGCG nanocomposite.

[0098] In Example 15 of the present invention, the active ingredient EGCG accounts for 3% of the EGCG nanocomposition.

[0099] Example 16 (Examples 16-18 have different types of flexible stabilizers)

[0100] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0101] (2) The 1.5% by mass of caprylic / capric triglyceride in Example 1 was replaced with 1.5% by mass of caprylic / capric / linoleic triglyceride, and the rest remained unchanged to prepare an EGCG nanocomposite.

[0102] In Example 16 of the present invention, the active ingredient EGCG accounts for 3% of the EGCG nanocomposition.

[0103] Embodiment 17

[0104] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0105] (2) The EGCG nanocomposite was prepared by replacing 1.5% by mass of caprylic / capric triglyceride in Example 1 with 1.5% by mass of linoleic acid, while keeping the rest unchanged.

[0106] In Example 17 of the present invention, the active ingredient EGCG accounts for 3% of the EGCG nanocomposition.

[0107] Embodiment 18

[0108] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0109] (2) The EGCG nanocomposite was prepared by replacing 1.5% by mass of caprylic / capric triglyceride in Example 1 with 1.5% by mass of octyl dodecanol, while keeping the rest unchanged.

[0110] In Example 18 of the present invention, the active ingredient EGCG accounts for 3% of the EGCG nanocomposition.

[0111] Example 19 (Examples 19-21 have different amounts of flexible stabilizer added)

[0112] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0113] (2) The mass percentage of 1.5% caprylic acid / capric acid triglyceride in Example 1 was replaced with the mass percentage of 0.5% caprylic acid / capric acid triglyceride, and the mass percentage of 60.05% deionized water was replaced with the mass percentage of 61.05% deionized water, and the rest remained unchanged, so that the total mass percentage was 100%. The subsequent treatment method remained unchanged to prepare the EGCG nanocomposite.

[0114] In Example 19 of the present invention, the proportion of the active ingredient EGCG in the EGCG nanocomposition is 3%.

[0115] Embodiment 20

[0116] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0117] (2) The mass percentage of 1.5% caprylic acid / capric acid triglyceride in Example 1 was replaced with the mass percentage of 1.0% caprylic acid / capric acid triglyceride, and the mass percentage of 60.05% deionized water was replaced with the mass percentage of 60.55% deionized water, and the rest remained unchanged, so that the total mass percentage was 100%. The subsequent treatment method remained unchanged to prepare the EGCG nanocomposite.

[0118] In Example 20 of the present invention, the active ingredient EGCG accounts for 3% of the EGCG nanocomposition.

[0119] Embodiment 21

[0120] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0121] (2) The mass percentage of 1.5% caprylic acid / capric acid triglyceride in Example 1 was replaced with the mass percentage of 2.0% caprylic acid / capric acid triglyceride, and the mass percentage of 60.05% deionized water was replaced with the mass percentage of 59.55% deionized water, and the rest remained unchanged, so that the total mass percentage was 100%. The subsequent treatment method remained unchanged to prepare the EGCG nanocomposite.

[0122] In Example 21 of the present invention, the active ingredient EGCG accounts for 3% of the EGCG nanocomposition.

[0123] Example 22 (Examples 22-23 have different amounts of nanocomposite precursor added)

[0124] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0125] (2) The 5% by mass percentage of the nanocomposite precursor in Example 1 was replaced with a 1% by mass percentage of the nanocomposite precursor, and the 60.05% by mass percentage of deionized water was replaced with a 64.05% by mass percentage of deionized water, and the rest remained unchanged, so that the total mass percentage was 100%. The subsequent treatment method remained unchanged to prepare the EGCG nanocomposite.

[0126] In Example 22 of the present invention, the active ingredient EGCG accounts for 0.6% in the EGCG nanocomposition.

[0127] Embodiment 23

[0128] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0129] (2) The 5% by mass percentage of the nanocomposite precursor in Example 1 was replaced with a 10% by mass percentage of the nanocomposite precursor, and the 60.05% by mass percentage of deionized water was replaced with a 55.05% by mass percentage of deionized water, and the rest remained unchanged, so that the total mass percentage was 100%. The subsequent treatment method remained unchanged to prepare the EGCG nanocomposite.

[0130] In Example 23 of the present invention, the active ingredient EGCG accounts for 6% of the EGCG nanocomposition.

[0131] Example 24 (Examples 24-25 have different types and addition amounts of other materials, which are limited in scope)

[0132] The difference between this embodiment and embodiment 1 is:

[0133] (1) The nanocomposite precursor comprises the following components in mass percentage: 5% dipalmitoylphosphatidylcholine, 10% EGCG, 10% methanol, 5% D-sorbitol, and 70% deionized water. The rest remain unchanged to obtain a nanocomposite precursor. In the nanocomposite precursor of this embodiment, in terms of mass percentage, dipalmitoylphosphatidylcholine: EGCG: D-sorbitol = 25%: 50%: 25%.

[0134] (2) The EGCG nanocomposite comprises the following components in percentage by mass: 0.3% palmitoylphosphatidylglycerol, 0.15% cholesterol, 1.5% caprylic / capric triglyceride, 5% 1,3-propylene glycol, 5% ethoxydiglycol, 5% nanocomposite precursor, and 83.05% deionized water. The rest remains unchanged to obtain the EGCG nanocomposite.

[0135] In Example 24 of the present invention, the proportion of the active ingredient EGCG in the EGCG nanocomposition is 2.5%.

[0136] Embodiment 25

[0137] The difference between this embodiment and embodiment 1 is:

[0138] (1) The nanocomposite precursor comprises the following components in mass percentage: 5% egg yolk lecithin, 20% EGCG, 50% chloroform, 5% xylitol, and 20% deionized water. The rest remain unchanged to obtain the nanocomposite precursor. In the nanocomposite precursor of this embodiment, in terms of mass percentage, egg yolk lecithin: EGCG: xylitol = 25%: 66.7%: 25%.

[0139] (2) The EGCG nanocomposite comprises the following components in percentage by mass: 0.3% dipalmitoylphosphatidylcholine, 0.15% cholesterol, 1.5% caprylic / capric triglyceride, 35% 1,2-butylene glycol, 15% polyethylene glycol (Mn=400), 5% nanocomposite precursor, and 43.05% deionized water. The rest remain unchanged to obtain the EGCG nanocomposite.

[0140] In Example 25 of the present invention, the proportion of the active ingredient EGCG in the EGCG nanocomposition is 3.3%. Comparative Example 1 (Traditional liposome-soy lecithin-monolayer)

[0141] Soybean lecithin was used as the wall material and the thin film method was used to prepare traditional liposomes. Based on the weight of the feed, 1.5g of soybean lecithin, 0.15g of cholesterol, and 3g of EGCG were dissolved in 30g of anhydrous ethanol, and stirred (at a speed of 300rpm) for 30min until all the raw materials were dissolved to obtain the alcohol phase. The alcohol phase was subjected to a rotary evaporation operation to remove anhydrous ethanol, with a rotary evaporation speed of 150rpm, a rotary evaporation temperature of 40°C, and a rotary evaporation time of 2h. At this time, a layer of light yellow phospholipid film remained on the wall of the rotary evaporation container. 95.35g of deionized water was added to the rotary evaporation container, and the phospholipid film was hydrated by stirring (at a speed of 300rpm) for 30min until the phospholipid film on the container wall completely fell off to obtain the EGCG traditional liposomes.

[0142] In Comparative Example 1 of the present invention, the proportion of the functional active ingredient EGCG in the EGCG nanocomposition is consistent with that in Example 1, which is 3%.

[0143] Comparative Example 2 (Traditional Liposome-Hydrogenated Lecithin-Monolayer)

[0144] Using hydrogenated lecithin as the wall material, traditional liposomes were prepared by the thin film method. Based on the weight of the feed, 1.5g of hydrogenated lecithin, 0.15g of cholesterol, and 3g of EGCG were dissolved in 30g of anhydrous ethanol, and stirred (at a speed of 300rpm) for 30min until all the raw materials were dissolved to obtain the alcohol phase. The alcohol phase was subjected to a rotary evaporation operation to remove anhydrous ethanol, with a rotary evaporation speed of 150rpm, a rotary evaporation temperature of 40°C, and a rotary evaporation time of 2h. At this time, a layer of light yellow phospholipid film remained on the wall of the rotary evaporation container. 95.35g of deionized water was added to the rotary evaporation container, and stirred (at a speed of 300rpm) for 30min to hydrate the phospholipid film until the phospholipid film on the container wall completely fell off to obtain EGCG traditional liposomes.

[0145] In Comparative Example 2 of the present invention, the proportion of the functional active ingredient EGCG in the EGCG nanocomposition remains consistent with that in Example 1, which is 3%.

[0146] Comparative Example 3 (rigid ligand only)

[0147] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0148] (2) The EGCG nanocomposite was prepared by replacing 1.5% by mass of caprylic / capric triglyceride in Example 1 with 1.5% by mass of deionized water, while keeping the rest unchanged and the subsequent treatment method unchanged.

[0149] Compared with Example 1, the difference is that in Comparative Example 3, only the rigid film material stabilizer cholesterol is added, and no flexible film material stabilizer is added.

[0150] Comparative Example 4 (flexible ligand only)

[0151] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0152] (2) The EGCG nanocomposite was prepared by replacing 0.15% by mass of cholesterol in Example 1 with 0.15% by mass of deionized water, while keeping the rest unchanged and the subsequent treatment method unchanged.

[0153] Compared with Example 1, the difference is that in Comparative Example 4, only caprylic / capric triglyceride, a flexible film material stabilizer, is added, but no rigid film material stabilizer is added.

[0154] Comparative Example 5 (without adding membrane stabilizer)

[0155] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0156] (2) The 0.15% by mass of cholesterol and 1.5% by mass of caprylic / capric triglyceride in Example 1 were replaced with 1.65% by mass of deionized water, while the rest remained unchanged, and the subsequent treatment method remained unchanged to prepare an EGCG nanocomposite.

[0157] Compared with Example 1, the difference is that no membrane material stabilizer is added in Comparative Example 5.

[0158] Comparative Example 6 (EGCG was added during the second step of phospholipid self-assembly)

[0159] (1) The 15% by mass EGCG in Example 1 was replaced with 15% by mass deionized water, while the rest remained unchanged, to prepare a nanocomposite precursor.

[0160] (2) 0.3% hydrogenated lecithin, 0.15% cholesterol, 1.5% caprylic / capric triglyceride and 3% EGCG were added to a mixed solution of 25% glycerol and 10% 1,2-hexanediol, and stirred at 30°C (speed of 300 rpm) for 30 min until the above raw materials were fully dissolved to obtain an alcohol phase. Under the condition of maintaining 30°C, 60.05% deionized water was uniformly added to the alcohol phase at a drop rate of 3 ml / min. After the drop addition was completed, stirring was continued at 30°C (speed of 300 rpm) for 15 min to obtain a mixed solution. The mixed solution was dispersed by high-speed shear (10000 rpm) for 20 min; then it was homogenized by high-pressure microfluidization, with a homogenization pressure of 80 MPa and a homogenization number of 4 times to obtain an EGCG nanocomposite.

[0161] In Comparative Example 6 of the present invention, the proportion of the active ingredient EGCG in the EGCG nanocomposition is 3%. Comparative Example 7 (the encapsulation technology is not used, and EGCG is added exogenously after the nanocomposition is prepared)

[0162] (1) The 15% by mass EGCG in Example 1 was replaced with 15% by mass deionized water, while the rest remained unchanged, to prepare a nanocomposite precursor.

[0163] (2) The preparation steps of the nanocomposite are the same as those in Example 1.

[0164] (3) EGCG with a mass percentage of 3% was added to the nanocomposition with a mass percentage of 97%, and stirred (rotation speed of 300 rpm) at 30° C. for 30 min to obtain an EGCG composition.

[0165] Comparative Example 8 (No nanocomposite precursor, one-step phospholipid encapsulation of EGCG)

[0166] 0.3% hydrogenated lecithin, 0.15% cholesterol, 1.5% caprylic / capric triglyceride, and 3% EGCG were added to a mixed solution of 25% glycerol and 10% 1,2-hexanediol by mass, and stirred (at a speed of 300 rpm) for 30 minutes until the above raw materials were fully dissolved to obtain an alcohol phase. The above alcohol phase was uniformly added dropwise to 60.05% deionized water at a drop rate of 3 ml / min. After the addition was completed, stirring was continued (at a speed of 300 rpm) for 15 minutes to obtain a mixed solution. The mixed solution was dispersed by high-speed shearing (10000 rpm) for 20 minutes; then subjected to high-pressure microfluidization homogenization treatment, the homogenization pressure was 80 MPa, and the number of homogenizations was 4 times. The EGCG nanocomposite was obtained.

[0167] Compared with Example 1, the difference is that in Comparative Example 8, a one-step phospholipid encapsulation method is used to prepare the EGCG nanocomposition. In Comparative Example 8 of the present invention, the active ingredient EGCG accounts for 3% of the EGCG nanocomposition. Comparative Example 9 (EGCG is dissolved in the water phase and then mixed with the alcohol phase)

[0168] (1) Preparation of nanocomposite precursor: 5.0% soybean lecithin was added to 30% anhydrous ethanol at 60°C, and stirred at 300 rpm for 30 min until the above raw materials were fully dissolved to obtain an organic phase. 5% maltitol and 15% EGCG were added to 45% deionized water at 60°C, and stirred at 300 rpm for 30 min until the above raw materials were fully dissolved to obtain an aqueous phase. While maintaining the temperature at 60°C, the organic phase was uniformly added dropwise to the aqueous phase at a drop rate of 3 ml / min. After the dropwise addition was completed, the mixture was stirred at 60°C for 15 min (at a speed of 300 rpm) to obtain a mixed solution. The obtained mixed solution was subjected to a rotary evaporation operation to remove anhydrous ethanol at a rotary evaporation speed of 150 rpm, a rotary evaporation temperature of 40°C, and a rotary evaporation time of 2 h. After freeze drying for 48 h, a nanocomposite precursor was obtained. In the nanocomposite precursor, calculated by mass percentage, phospholipid: EGCG: maltitol = 20%: 60%: 20%.

[0169] (2) The preparation steps of the EGCG nanocomposite are the same as those in Example 1.

[0170] Compared with Example 1, the difference is that in the preparation process of the nanocomposite precursor in Comparative Example 9, EGCG is first dissolved in deionized water and then mixed with alcohol.

[0171] Comparative Example 10 (Chitosan Surface Modification)

[0172] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0173] (2) 0.3% by mass of hydrogenated lecithin was replaced with 0.3% by mass of chitosan, while the rest remained unchanged, and the subsequent treatment method remained unchanged to prepare a chitosan-modified EGCG nanocomposite.

[0174] Compared with Example 1, the difference is that in Comparative Example 10, chitosan is used to modify the nanocomposite precursor.

[0175] Comparative Example 11 (Surface Modification of Gum Arabic)

[0176] (1) The preparation steps of the nanocomposite precursor are the same as those in Example 1.

[0177] (2) 0.3% by mass of hydrogenated lecithin was replaced with 0.3% by mass of gum arabic, while the rest remained unchanged, and the subsequent treatment method remained unchanged to prepare the gum arabic modified EGCG nanocomposite.

[0178] Compared with Example 1, the difference is that in Comparative Example 11, gum arabic is used to modify the nanocomposite precursor. Comparative Example 12 (EGCG Nanoemulsion)

[0179] Mix 3% by mass EGCG and 15% by mass caprylic / capric triglyceride and heat to 85°C until EGCG is completely dissolved, and then add 10% by mass butanediol to obtain an oil phase component. Add the above oil phase dropwise to 72% by mass deionized water at a dropping speed of 3 ml / min. After the addition is completed, continue stirring (speed of 300 rpm) for 15 minutes to obtain a mixed solution. Disperse the mixed solution by high-speed shear (10000 rpm) for 20 minutes; then treat it with high-pressure microfluidization homogenization at a homogenization pressure of 80 MPa and 4 times to obtain an EGCG nanoemulsion. Comparative Example 13 (3% EGCG aqueous solution)

[0180] 3% by mass of EGCG was added into 97% by mass of deionized water, and the mixture was stirred (at a rotation speed of 300 rpm) for 15 min until EGCG was completely dissolved, thereby obtaining an EGCG aqueous solution.

[0181] Test Example 1 (Particle Size Test)

[0182] The particle sizes of the samples of Examples 1-25 and Comparative Examples 1-12 were characterized by using a Malvern Nano-ZS90 dynamic light scattering particle size analyzer. The test angle was 90° and the test temperature was 25°C. Three parallel experiments were performed for each group of experiments, and the arithmetic mean of the experimental results was taken.

[0183] Test Example 2 (EGCG encapsulation efficiency test)

[0184] The EGCG encapsulation efficiency of the samples of Examples 1-25 and Comparative Examples 1-12 was determined. 200 μL of the sample EGCG nanocomposition was taken, and ultrafiltration centrifuged (9000 rpm, 30 min). 5 μL of the filtrate was taken and the EGCG content in the filtrate was determined by high performance liquid chromatography (HPLC, Shimadzu, Japan), and the content of EGCG not encapsulated in the EGCG nanocomposition was obtained. Another EGCG nanocomposition was taken, and a mixed solution of methanol and water was added. Ultrasonic demulsification was performed for 30 min according to sample: methanol: water = 1:4:5 (v / v). After filtering with a 0.45 μm organic filter membrane, 5 μL of the sample solution was taken and the content of EGCG was determined by high performance liquid chromatography (HPLC, Shimadzu, Japan), and the content of EGCG in the EGCG nanocomposition was obtained. The EGCG encapsulation efficiency (EE) in the EGCG nanocomposition was calculated according to formula (1). The analytical column used in the HPLC system was a non-polar C18 column, the mobile phase was acetonitrile, the flow rate was 1.0 ml / min, the column temperature was 30°C, and each group of experiments was conducted three times in parallel, and the experimental results were taken as the arithmetic mean.

[0185]

[0186] C1 represents the concentration of unencapsulated EGCG in the sample; C0 represents the concentration of EGCG in the sample after ultrasonic demulsification of a mixed solution of methanol and deionized water.

[0187] Test Example 3 (Storage Stability Test)

[0188] After the samples of Examples 1-25 and Comparative Examples 1-12 were left standing at room temperature for 1 month, 2 months and 3 months, the particle size and encapsulation efficiency of the samples were measured according to the methods described in Test Example 1 and Test Example 2, respectively, to test the storage stability of the samples.

[0189] Table 1 Particle size characterization and encapsulation efficiency test of samples and storage stability at room temperature for 0-3 months

[0190]

[0191]

[0192]

[0193]

[0194]

[0195] Table 1 shows the particle size characterization and encapsulation efficiency test results of Examples 1-25 and Comparative Examples 1-12, as well as the changes in particle size and encapsulation efficiency of Examples 1-25 and Comparative Examples 1-12 after standing at room temperature for 1 month, 2 months, and 3 months.

[0196] Comparative Examples 1-5 show that, in the nanocomposite precursor, the addition amount of soybean lecithin is different, and the particle size, encapsulation efficiency and storage stability of the EGCG nanocomposite finally prepared are different. In Examples 1-5, the mass percentages of soybean lecithin are 5%, 1%, 3%, 7% and 10% respectively. As the addition amount of soybean lecithin in the nanocomposite precursor gradually increases, the particle size of the EGCG nanocomposite finally prepared first decreases and then increases, and the encapsulation efficiency first increases and then decreases. When the mass percentage of soybean lecithin in the nanocomposite precursor is 5% (Example 1), the particle size of the EGCG nanocomposite finally prepared is the smallest, which is 83.4nm, and the encapsulation efficiency is the highest, which is 89.2%. In addition, the storage stability of the EGCG nanocomposite in Example 1 is better than that of Examples 2-5. After the sample is stored at room temperature for three months, the particle size change rate and encapsulation efficiency change rate of the EGCG nanocomposite are the smallest, which are 3.77% and 4.31% respectively. Therefore, in the sample of Example 1, its encapsulation effect on EGCG is the best.

[0197] Comparative Example 1 and Examples 6-9 show that the addition amount of hydrogenated lecithin is different, and the particle size, encapsulation efficiency and storage stability of the EGCG nanocomposite finally prepared are different. In Example 1 and Examples 6-9, the mass percentages of hydrogenated lecithin are 0.3%, 0.1%, 0.5%, 0.7% and 1.0%, respectively. As the addition amount of hydrogenated lecithin gradually increases, the particle size of the EGCG nanocomposite gradually increases, while the encapsulation efficiency first increases and then decreases. When the mass percentage of hydrogenated lecithin in the EGCG nanocomposite is 0.3% (Example 1), the encapsulation effect of EGCG is optimal.

[0198] By comparing Example 1 and Examples 10-12, it can be seen that the types of rigid film material stabilizers are different, and the particle size, encapsulation efficiency and storage stability of the EGCG nanocomposition finally prepared are different. In Example 1 and Examples 10-12, the rigid film material stabilizers are cholesterol, sodium cholate, resorcinol, and phenylalanine, respectively. The results show that when the rigid film material stabilizer is cholesterol, the final product has the best encapsulation effect on EGCG.

[0199] By comparing Example 1 and Examples 13-15, it can be seen that the amount of rigid film material stabilizer added will affect the particle size, encapsulation rate and storage stability of the final product. In Example 1 and Examples 13-15, the mass percentages of the rigid film material stabilizer are 0.15%, 0.1%, 0.2% and 0.3%, respectively. The results show that as the amount of rigid film material stabilizer added increases, the particle size of the product gradually increases, while the encapsulation rate first increases and then decreases. When the mass percentage of the rigid film material stabilizer in the EGCG nanocomposite is 0.15% (Example 1), the encapsulation effect of EGCG is optimal.

[0200] By comparing Example 1 and Examples 16-18, it can be seen that the type of flexible film material stabilizer will affect the particle size, encapsulation efficiency and storage stability of the final product. In Example 1 and Examples 16-18, the flexible film material stabilizers are caprylic / capric triglyceride, caprylic / capric / linoleic triglyceride, linoleic acid, and octyldodecanol, respectively. The results show that when caprylic / capric triglyceride is selected as the flexible film material stabilizer, the final product has the best encapsulation effect on EGCG.

[0201] By comparing Example 1 and Examples 19-21, it can be seen that the amount of flexible film material stabilizer added will affect the particle size and encapsulation rate of the final product. In Example 1 and Examples 19-21, the mass percentages of the flexible film material stabilizer are 1.5%, 0.5%, 1.0% and 2.0%, respectively. The results show that as the amount of flexible film material stabilizer added increases, the particle size of the product first decreases and then increases, while the encapsulation rate first increases and then decreases. When the mass percentage of the flexible film material stabilizer in the EGCG nanocomposition is 1.5% (Example 1), the encapsulation effect of EGCG is optimal.

[0202] By comparing Example 1, Example 22 and Example 23, it can be seen that the particle size, encapsulation efficiency and storage stability of the EGCG nanocomposite finally prepared are different when the amount of the nanocomposite precursor added is different. In Example 1, Example 22 and Example 23, the mass percentage of the nanocomposite precursor is 5%, 1% and 10% respectively. The results show that as the amount of the nanocomposite precursor added increases, the particle size of the product first decreases and then increases, and the encapsulation efficiency first increases and then decreases. When the mass percentage of the nanocomposite precursor in the EGCG nanocomposite is 5% (Example 1), the encapsulation effect of EGCG is optimal.

[0203] By comparing Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that compared with traditional liposomes, the present application adopts a two-step phospholipid self-assembly method, first preparing a nanocomposite precursor to encapsulate EGCG, and then self-assembling and protecting the nanocomposite precursor with hydrogenated lecithin. The EGCG nanocomposite finally prepared has a smaller particle size, a higher encapsulation rate, and optimal storage stability.

[0204] By comparing Example 1 and Examples 3-5, it can be seen that compared with the samples using only rigid film material stability (Comparative Example 3), or only flexible film material stabilizer (Comparative Example 4), or no film material stabilizer (Comparative Example 5), Example 1 of the present application simultaneously uses rigid and flexible film material stabilizers to compound and regulate the phospholipid membrane, and the EGCG nanocomposition finally prepared has a smaller particle size, a higher encapsulation rate, and the best storage stability.

[0205] Comparison of Example 1, Example 6 and Example 7 shows that, during the sample preparation process, the addition step of EGCG will affect the particle size, encapsulation efficiency and storage stability of the final product. Compared with adding EGCG during the second step of phospholipid self-assembly of the EGCG nanocomposition in Example 6, or adding EGCG after the preparation of the EGCG nanocomposition in Example 7, in Example 1 of the present application, EGCG is first encapsulated in a prefabricated nanocomposition precursor, and the EGCG nanocomposition is prepared by a two-step phospholipid self-assembly method, and the particle size of the final sample is smaller, the encapsulation efficiency is higher, and the storage stability is better.

[0206] By comparing Example 1 and Comparative Example 8, it can be seen that compared with the one-step encapsulation method of EGCG, Example 1 of the present application first encapsulates EGCG with a prefabricated nanocomposition precursor, and prepares the EGCG nanocomposition by a two-step phospholipid self-assembly method. The final sample has a smaller particle size, a higher encapsulation rate, and better storage stability. That is, the method used in Example 1 of the present application has a better encapsulation effect on EGCG.

[0207] By comparing Example 1 and Comparative Example 9, it can be seen that compared with the method of adding EGCG to the aqueous phase and mixing it with the oil phase to prepare the nanocomposite precursor, the method of adding EGCG to the oil phase and mixing it with the aqueous phase to prepare the nanocomposite precursor in Example 1 of the present application, the EGCG nanocomposite finally obtained has a smaller particle size, a higher encapsulation rate, and better storage stability.

[0208] By comparing Example 1, Example 10 and Example 11, it can be seen that compared with the use of chitosan (Comparative Example 10) and gum arabic (Comparative Example 11) to modify the nanocomposition precursor, hydrogenated lecithin is used to protect the nanocomposition precursor in Example 1 of the present application, and the EGCG nanocomposition finally obtained has a smaller particle size, a higher encapsulation rate, and better storage stability.

[0209] By comparing Example 1 and Comparative Example 12, it can be seen that compared with the use of nanoemulsion dosage form to encapsulate EGCG, in Example 1 of the present application, EGCG is first encapsulated in a prefabricated nanocomposition precursor, and the EGCG nanocomposition is prepared by a two-step phospholipid self-assembly method. The final sample has a smaller particle size, a higher encapsulation rate, and better storage stability.

[0210] Test Example 4 (Vesicle Deformability Test)

[0211] 1 ml of EGCG nanocomposition was loaded into a syringe and inserted into the extruder sleeve fixed on a vertical stand, with the needle facing down and the plunger section in contact with a 50 N loading unit. The rigid probe was in contact with the syringe plunger at a constant speed of 1 mm / s, forcing the EGCG nanocomposition to pass through the 50 nm polycarbonate film in the extruder sleeve. The polycarbonate film was pretreated with ultrapure water before each experiment.

[0212] Malvern Nano-ZS90 dynamic light scattering particle size was used to characterize the particle size of the EGCG nanocomposite before and after extrusion. The test angle was 90° and the test temperature was 25°C. Three parallel experiments were conducted for each group of experiments, and the arithmetic mean of the experimental results was taken. The particle size change rate of the EGCG nanocomposite before and after extrusion was calculated according to formula (2).

[0213]

[0214] Among them, Dh0 represents the particle size of the EGCG nanocomposite before extrusion; D he It represents the particle size of the EGCG nanocomposite after extrusion.

[0215] Table 2 Particle size changes of samples before and after extrusion

[0216]

[0217]

[0218] As shown in Table 2, it can be seen from the comparative examples 1-5 that in the nanocomposite precursor, the amount of soybean lecithin added is different, and the deformation ability of the EGCG nanocomposite finally prepared is different. As the amount of soybean lecithin added in the nanocomposite precursor gradually increases, the deformation ability of the EGCG nanocomposite finally prepared is first enhanced and then weakened. When the mass percentage of soybean lecithin in the nanocomposite precursor is 5% (Example 1), the deformation ability of the EGCG nanocomposite finally prepared is the best, and the particle size change rate of the sample before and after being squeezed is the smallest, which is 3.08%. Therefore, the sample in Example 1 can effectively avoid the sudden release of EGCG caused by its structure being destroyed, that is, the EGCG nanocomposite in Example 1 has better extrusion resistance and stability.

[0219] Comparing Example 1 and Examples 6-9, it can be seen that the deformation ability of the EGCG nanocomposite finally prepared is different when the amount of hydrogenated lecithin added is different. As the amount of hydrogenated lecithin added gradually increases, the deformation ability of the EGCG nanocomposite finally prepared first increases and then weakens. When the mass percentage of hydrogenated lecithin in the EGCG nanocomposite is 0.3% (Example 1), the deformation ability of the EGCG nanocomposite finally prepared is the best.

[0220] By comparing Example 1 and Examples 10-12, it can be seen that the deformation ability of the EGCG nanocomposite finally prepared is different due to the different types of rigid film material stabilizers. In Example 1 and Examples 10-12, the rigid film material stabilizers are cholesterol, sodium cholate, resorcinol, and phenylalanine, respectively. The results show that when the rigid film material stabilizer is cholesterol, the final EGCG nanocomposite has the best deformation ability, better extrusion resistance, and better stability.

[0221] By comparing Example 1 and Examples 13-15, it can be seen that the amount of rigid film material stabilizer added will affect the deformation ability of the final product. The results show that as the amount of rigid film material stabilizer added increases, the deformation ability of the EGCG nanocomposite prepared finally increases first and then weakens. When the mass percentage of the rigid film material stabilizer in the EGCG nanocomposite is 0.15% (Example 1), the final EGCG nanocomposite has the best deformation ability, better extrusion resistance, and better stability.

[0222] By comparing Example 1 and Examples 16-18, it can be seen that the type of flexible film material stabilizer will affect the deformation ability of the final product. The results show that when the flexible film material stabilizer is caprylic / capric triglyceride (Example 1), the final product has the best deformation ability, better extrusion resistance and better stability.

[0223] By comparing Example 1 and Examples 19-21, it can be seen that the amount of flexible film material stabilizer added will affect the deformation ability of the final product. The results show that as the amount of flexible film material stabilizer added increases, the deformation ability of the product first increases and then weakens. When the mass percentage of the flexible film material stabilizer in the EGCG nanocomposite is 1.5% (Example 1), the EGCG nanocomposite finally prepared has the best deformation ability, better extrusion resistance, and better stability.

[0224] By comparing Example 1, Example 22 and Example 23, it can be seen that the deformation ability of the EGCG nanocomposite finally prepared is different when the amount of the nanocomposite precursor added is different. The results show that as the amount of the nanocomposite precursor added increases, the deformation ability of the product first increases and then decreases. When the mass percentage of the nanocomposite precursor in the EGCG nanocomposite is 5% (Example 1), the EGCG nanocomposite finally prepared has the best deformation ability, better extrusion resistance and better stability.

[0225] By comparing Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that compared with traditional liposomes, the present application adopts a two-step phospholipid self-assembly method, first preparing a nanocomposite precursor to encapsulate EGCG, and then self-assembling and protecting the nanocomposite precursor with hydrogenated lecithin. The EGCG nanocomposite finally prepared has the best deformation ability, better extrusion resistance and better stability.

[0226] By comparing Example 1 and Comparative Examples 3-5, it can be seen that compared with the samples using only rigid film material stability (Comparative Example 3), or only flexible film material stabilizer (Comparative Example 4), or no film material stabilizer (Comparative Example 5), the present application simultaneously uses rigid and flexible film material stabilizers to compound and regulate the phospholipid membrane, and the EGCG nanocomposite finally prepared has the best deformation ability, better extrusion resistance, and better stability.

[0227] Comparison of Example 1, Example 6 and Example 7 shows that the addition step of EGCG during the preparation of the sample will affect the deformation ability of the final product. Compared with adding EGCG during the second step of phospholipid self-assembly of the EGCG nanocomposition in Example 6, or adding EGCG after the preparation of the EGCG nanocomposition in Example 7, in Example 1 of the present application, EGCG was first wrapped in a prefabricated nanocomposition precursor, and the EGCG nanocomposition was prepared by a two-step phospholipid self-assembly method. The final sample has the best deformation ability, better extrusion resistance, and better stability.

[0228] By comparing Example 1 and Comparative Example 8, it can be seen that compared with the one-step encapsulation method of EGCG, Example 1 of the present application adopts the method of first encapsulating EGCG with a prefabricated nanocomposition precursor, and preparing the EGCG nanocomposition through a two-step phospholipid self-assembly method. The final sample has the best deformation ability, better extrusion resistance, and better stability.

[0229] By comparing Example 1 and Comparative Example 9, it can be seen that compared with the method of adding EGCG to the water phase and mixing it with the oil phase to prepare the nanocomposite precursor, the method of adding EGCG to the oil phase and mixing it with the water phase to prepare the nanocomposite precursor in Example 1 of the present application, the EGCG nanocomposite finally obtained has the best deformation ability, better extrusion resistance and better stability.

[0230] By comparing Example 1, Example 10 and Example 11, it can be seen that compared with the use of chitosan (Comparative Example 10) and gum arabic (Comparative Example 11) to modify the nanocomposite precursor, hydrogenated lecithin is used to protect the nanocomposite precursor in Example 1 of the present application, and the EGCG nanocomposite finally obtained has the best deformation ability, better extrusion resistance and better stability.

[0231] Test Example 5 (Transdermal Absorption Test)

[0232] The transdermal absorption (permeation promotion) test was used to evaluate the transdermal absorption (permeation promotion) ability of the EGCG nanocompositions in Examples 1-21 and Comparative Examples 1-13, and the specific method is as follows:

[0233] In vitro transdermal experiments were performed using a vertical diffusion cell, with nude mouse skin as the model (abdominal skin, subcutaneous fat layer and blood vessels removed). The receiving solution was PBS solution. The skin piece was fixed between the supply cell and the receiving cell, with the skin layer facing up, and balanced for 20 minutes. The sample solution was added to the supply cell, and the receiving solution was taken after 1 hour, 4 hours, 8 hours, and 24 hours. The receiving solution was ultrasonically demulsified with a mixed solution of methanol and water, and ultrasonicated for 30 minutes according to the receiving solution: methanol: water = 1:4:5 (v / v). After filtering with a 0.45μm organic filter membrane, the EGCG content was determined by high performance liquid chromatography (HPLC, Shimadzu, Japan), and the cumulative permeation per unit area was calculated according to formula (3). Three parallel experiments were performed for each group of experiments, and the experimental results were taken as the arithmetic mean.

[0234]

[0235] Among them, Q n is the cumulative transmittance per unit area of ​​the sample at time t (μg / cm 2 ), A is the permeable area, C n is the measured value of EGCG concentration at time t, C i is the measured value of EGCG concentration sampled at time point t, V is the total volume of the receiving solution, and V0 is the sampling volume at each time point.

[0236] Table 3 Transdermal test results of samples

[0237]

[0238]

[0239] As shown in Table 3, it can be seen from the comparison of Examples 1-5 that in the nanocomposite precursor, the amount of soybean lecithin added is different, and the transdermal performance of the EGCG nanocomposite finally prepared is different. As the amount of soybean lecithin added in the nanocomposite precursor gradually increases, the transdermal performance of the EGCG nanocomposite finally prepared first increases and then decreases. When the mass percentage of soybean lecithin in the nanocomposite precursor is 5% (Example 1), the cumulative permeation amount per unit area of ​​EGCG in the final product at 1h, 4h, 8h and 24h is 4.31μg / cm 2 , 15.68μg / cm 2 , 28.12μg / cm 2 and 89.32 μg / cm 2 , which are higher than those of the samples in Examples 2-5, indicating that the transdermal performance of Example 1 is the best.

[0240] By comparing Example 1 and Examples 6-9, it can be seen that the transdermal performance of the EGCG nanocompositions prepared in the end is different when the amount of hydrogenated lecithin added is different. In Example 1 of the present application, the mass percentage of hydrogenated lecithin is 0.3%, and the cumulative permeation amount per unit area of ​​EGCG in the final product is the highest, indicating that Example 1 has the best transdermal performance.

[0241] By comparing Example 1 and Examples 10-15, it can be seen that the type and amount of rigid film material stabilizer affect the transdermal performance of the product. When cholesterol is selected as the rigid film material stabilizer and the mass percentage is 0.15% (Example 1), the cumulative permeation amount of EGCG per unit area in the final product is the highest, indicating that its transdermal performance is optimal.

[0242] By comparing Example 1 and Examples 16-21, it can be seen that the type and amount of the flexible film material stabilizer affect the transdermal performance of the product. When the rigid film material stabilizer is caprylic / capric triglyceride with a mass percentage of 1.5% (Example 1), the cumulative permeation amount of EGCG per unit area in the final product is the highest, indicating that its transdermal performance is optimal.

[0243] By comparing Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that compared with traditional liposomes, the present application adopts a two-step phospholipid self-assembly method, first preparing a nanocomposite precursor to encapsulate EGCG, and then self-assembling and protecting the nanocomposite precursor with hydrogenated lecithin. The cumulative permeation amount per unit area of ​​EGCG in the final product is the highest, indicating that its transdermal performance is optimal.

[0244] By comparing Example 1 and Comparative Examples 3-5, it can be seen that compared with the samples using only rigid membrane material stability (Comparative Example 3), or only flexible membrane material stabilizer (Comparative Example 4), or no membrane material stabilizer (Comparative Example 5), the present application simultaneously uses rigid and flexible membrane material stabilizers to compound and regulate the phospholipid membrane, and the cumulative permeation amount of EGCG per unit area in the final product is the highest, indicating that its transdermal performance is optimal.

[0245] By comparing Example 1, Example 6 and Example 7, it can be seen that compared with adding EGCG during the second step phospholipid self-assembly process of the EGCG nanocomposition in Example 6, or adding EGCG after the preparation of the EGCG nanocomposition in Example 7, in Example 1 of the present application, EGCG is first wrapped in a prefabricated nanocomposition precursor, and the EGCG nanocomposition is prepared by a two-step phospholipid self-assembly method. The cumulative permeation amount per unit area of ​​EGCG in the final product is the highest, indicating that its transdermal performance is optimal.

[0246] By comparing Example 1 and Comparative Example 8, it can be seen that compared with the one-step encapsulation method of EGCG, Example 1 of the present application adopts the method of first encapsulating EGCG with a prefabricated nanocomposition precursor, and preparing the EGCG nanocomposition by a two-step phospholipid self-assembly method. The cumulative permeation amount per unit area of ​​EGCG in the final product is the highest, indicating that its transdermal performance is optimal.

[0247] By comparing Example 1 and Comparative Example 9, it can be seen that compared with the method of adding EGCG to the aqueous phase and mixing it with the oil phase to prepare the nanocomposite precursor, the method of adding EGCG to the oil phase and mixing it with the aqueous phase to prepare the nanocomposite precursor in Example 1 of the present application has the highest cumulative permeation amount of EGCG per unit area in the final product, indicating that its transdermal performance is optimal.

[0248] By comparing Example 1, Example 10 and Example 11, it can be seen that compared with the use of chitosan (Comparative Example 10) and gum arabic (Comparative Example 11) to modify the nanocomposite precursor, the use of hydrogenated lecithin to protect the nanocomposite precursor in Example 1 of the present application has the highest cumulative permeation amount per unit area of ​​EGCG in the final product, indicating that its transdermal performance is optimal.

[0249] By comparing Example 1, Example 12 and Example 13, it can be seen that compared with the use of nanoemulsion dosage form to encapsulate EGCG (Comparative Example 12) and EGCG aqueous solution (Comparative Example 13), in Example 1 of the present application, EGCG is first encapsulated in a prefabricated nanocomposition precursor, and the EGCG nanocomposition is prepared by a two-step phospholipid self-assembly method. The cumulative permeation amount per unit area of ​​EGCG in the final product is the highest, indicating that its transdermal performance is optimal.

[0250] Test Example 6 (Antioxidation—Cellular Reactive Oxygen Species ROS Inhibition Test)

[0251] Human skin keratinocytes (HaCaT) were digested and prepared into a cell suspension, which was then inoculated into a 96-well plate at 1.0×10 5 -2.0×10 5 The cells were cultured using DMEM medium. After 24 hours of culture, the medium was replaced, and a blank group (PBS buffer was added and no light was irradiated), a control group (PBS buffer was added and light was irradiated) and an experimental group (the samples of the embodiment and the comparative example were added, and the added amount was 10% of the amount of the cell culture medium) were set up respectively. The culture was continued for 24 hours, and then the control group and the experimental group were irradiated with UVA light (the light dose was 6-10 J / cm 2). After the illumination, the cell culture medium was removed, and the cells were washed with PBS three times. 100 μL of 10 μmol / L DCFH-DA was added to each well and placed in a CO2 incubator for 20 min. After the incubation, the cells were washed with PBS three times, and serum-free DMEM culture medium was added again. The ROS content was detected using a fluorescence microplate reader at an excitation wavelength of 488 nm and an emission wavelength of 525 nm. The relative level of cellular ROS was the ratio of the OD value of the experimental group (or the OD value of the control group) to the OD value of the blank group.

[0252] Table 4 Relative levels of ROS in HaCaT cells after light damage in sample treatment

[0253]

[0254]

[0255] As can be seen from Table 4, the relative levels of ROS in the HaCaT cells damaged by light of the EGCG nanocompositions prepared in Examples 1-21 are lower than those in the control group, indicating that they have good antioxidant properties and can reduce the damage of light damage. In addition, the relative levels of ROS in the HaCaT cells damaged by light of the EGCG nanocompositions prepared in Examples 1-21 are lower than those in Comparative Examples 1-13, indicating that Examples 1-21 have better antioxidant properties, among which the relative level of ROS in the HaCaT cells damaged by light of the EGCG nanocomposition in Example 1 is the lowest, which is 102.2%, indicating that the EGCG nanocomposition in Example 1 has the best antioxidant properties and can effectively reduce the damage of light damage.

[0256] Test Example 7 DNA repair damage - anti-photoaging

[0257] (1) DNA double-strand breaks are considered the most serious DNA damage. H2AX, the full name of which is H2A histone family member X, can also be referred to as H2AX, which is one of the variants of chromosome histone H2A. When the double-strand DNA breaks in cells, H2AX will be phosphorylated to form phosphorylated H2AX, namely γ-H2AX. The level of γ-H2AX can clearly reflect the degree of DNA damage and repair. It is widely used in the study of DNA damage and cell apoptosis and has become an important DNA damage marker.

[0258] In this test case, the DNA damage repair experiment uses a DNA damage detection kit (γ-H2AX immunofluorescence method, mouse monoclonal antibody, green), which can be purchased directly from Shanghai Biyuntian Biotechnology Co., Ltd. Human skin keratinocytes (HaCaT) were digested and prepared into a cell suspension, which was then inoculated into a 96-well plate, with 1.0×10 5 -2.0×105 The cells were cultured in DMEM medium for 24 hours, and then the blank control group and the experimental group were exposed to UVA light (the light dose was 6-10J / cm 2 ). After the illumination, remove the cell culture medium and wash with PBS three times. Collect the cells by centrifugation and wash once with PBS. After absorbing all the PBS, flick the cells appropriately. Add the fixative solution configured in the kit, gently suspend the cells, and fix for 10 minutes. Centrifuge, remove the fixative, and add the washing solution configured in the kit to wash once. Take a small amount of washing solution to resuspend the cells, drop it on the cover glass or slide to make a smear. After fully drying, wash twice with washing solution, add 1ml of immunostaining blocking solution, and block at room temperature for 15 minutes. Aspirate the immunostaining blocking solution, add 1mlγ-H2AX mouse monoclonal antibody, and incubate at room temperature for 1 hour. Wash 3 times with washing solution, add 1ml anti-mouse 488, and incubate at room temperature for 1 hour. Wash twice with washing solution, add 1ml cell nuclear staining solution (DAPI), stain at room temperature for 5 minutes, aspirate the cell nuclear staining solution, and wash 3 times with washing solution. Finally, the samples were photographed and analyzed using laser confocal microscopy.

[0259] The results of DNA damage repair (γ-H2AX method) of Example 1, Comparative Example 13 (EGCG aqueous solution) and vitamin C (VC) are as follows Figure 1 As shown. The results show that after the cells were irradiated with radiation (ultraviolet rays), DNA damage was caused. After being treated with the experimental group Example 1 and the comparative example 13, the green fluorescence content was significantly reduced and less than the VC group, indicating that the experimental group (Example 1 and comparative example 13) had a better repair effect on DNA-damaged cells than the VC control group. In addition, after being treated with Example 1, the green fluorescence content of the cells was significantly less than that of the comparative example 13, indicating that the EGCG nanocomposition in Example 1 had a better repair effect on DNA-damaged cells than the EGCG aqueous solution that had not been encapsulated.

[0260] Test Example 8 Protein carbonylation inhibition - skin yellowing effect test

[0261] Protein carbonylation is a non-enzymatic, irreversible carbonyl modification of proteins. The pathways for the formation of carbonyl proteins are divided into two categories based on whether ROS is involved: (1) ROS directly oxidizes protein side chain amino acids to form carbonyl proteins (i.e., free radical oxidation); (2) proteins form carbonyl proteins after lipid oxidation and non-enzymatic glycosylation (i.e., glycosylation).

[0262] Principle of indicator detection: DNPH staining: Protein carbonyl content is a sensitive indicator of protein oxidative damage. 2,4-dinitrophenylhydrazine (DNPH) colorimetry is a classic method for determining protein carbonyl content. The carbonyl content of oxidized protein increases, and the carbonyl group can react with 2,4-dinitrophenylhydrazine to generate 2,4-dinitrophenylhydrazone, which exhibits green fluorescence after fluorescent staining. The anti-carbonylation ability of the sample can be judged by analyzing the fluorescence intensity of the sample after use. The weaker the green fluorescence intensity, the less carbonylation product.

[0263] Protein carbonyl is an early marker of the oxidation modification of various amino acids in proteins. Its content indicates the extent of protein oxidative damage and is the main indicator for measuring protein oxidative damage. L929 cells (100,000 / well) in the logarithmic growth phase were planted in a 6-well plate. After adherence, each well was irradiated with ultraviolet light for 10 minutes. After ultraviolet irradiation, drugs were administered. Different wells were given samples of different categories at the same concentration. After 48 hours of drug administration, cells were treated. Carbonyl reacts with 2,4-dinitrophenylhydrazine to generate red 2,4-dinitrophenylhydrazone, which has a characteristic absorption peak at 370nm.

[0264] Among them, the cells that were not administered after 10 minutes of ultraviolet irradiation were used as the positive control group; the normal cells in the logarithmic growth phase, which were not irradiated with ultraviolet light and not administered, were used as the negative control group. The samples added to the experimental group were Example 1, Comparative Example 13 (EGCG aqueous solution) and vitamin C (VC). The results of the protein carbonylation inhibition experiment are shown in Figure 2. Figure 2 As shown. The results show that after the cells were irradiated with radiation (ultraviolet rays), the protein carbonylation content increased significantly. After being treated with the experimental group of Example 1 and the experimental group of Comparative Example 13, the protein carbonylation content decreased significantly and was less than that of the VC experimental group, indicating that the protein carbonylation inhibition effect of Example 1 and Comparative Example 13 was better than that of the VC experimental group, that is, EGCG was better than VC in terms of protein carbonylation inhibition. In addition, after being treated with the experimental group of Example 1, the protein carbonylation content was significantly lower than that of the experimental group of Comparative Example 13, indicating that the EGCG nanocomposition in Example 1 was better than the EGCG aqueous solution without encapsulation treatment in terms of protein carbonylation inhibition effect. Therefore, the EGCG nanocomposition of the present invention can play an anti-photoaging and skin yellowing role.

Claims

1. A method for preparing an EGCG nanocomposition having strong antioxidant and anti-photoaging effects, characterized in that: The steps include: (1) Preparation of nanocomposite precursors: The phospholipid and EGCG are added to an organic solvent and stirred evenly to obtain an organic phase; the polyol is added to water and stirred evenly to obtain an aqueous phase; the organic phase is uniformly added dropwise to the aqueous phase, and after the addition is completed, the stirring is continued to obtain a mixed solution; the organic solvent is removed from the obtained mixed solution; and the mixed solution is dried to obtain a nanocomposite precursor; In terms of mass percentage, the phospholipid content in the mixed solution is 1%-10%; (2) Preparation of dual phospholipid nanocomposites: Adding phospholipids, rigid membrane material stabilizers and flexible membrane material stabilizers to polyols, stirring evenly to obtain an alcohol phase; adding the nanocomposite precursor to water, stirring and dispersing evenly to obtain an aqueous phase; dropping the aqueous phase into the alcohol phase at a uniform speed, and continuing to stir after the dropping is completed to obtain a mixed solution; The mixed solution is subjected to nano-processing to obtain an EGCG nano-composition, wherein the mass percentage of EGCG in the EGCG nano-composition is 0.6%-6.0%; the nano-processing comprises high-speed shear dispersion processing and / or microfluidization homogenization processing; In terms of mass percentage, the phospholipid content in the mixed solution is 0.1%-1.0%, the rigid membrane material stabilizer content is 0.1%-0.3%, and the flexible membrane material stabilizer content is 0.5%-2.0%; The molecular structure of the rigid film material stabilizer contains a polycyclic structural unit or a benzene ring structural unit; the molecular structure of the flexible film material stabilizer is a straight chain type or a straight chain compound; The rigid film material stabilizer includes one or more of cholesterol, phytosterol, sodium cholate, vitamin D, resorcinol, phenylalanine, and phenylpropanol; The flexible film material stabilizer includes one or more of caprylic acid / capric acid triglyceride, caprylic acid / capric acid / linoleic acid triglyceride, caprylic acid / capric acid / lauric acid triglyceride, oleic acid, linoleic acid, octyldodecanol, and octyldodecanol oleate.

2. The preparation method according to claim 1, characterized in that: The mass percentage of EGCG in the EGCG nanocomposition is 3±2%.

3. The preparation method according to claim 1 or 2, characterized in that: In terms of mass percentage, In step (1), the mixed solution comprises 5±2% phospholipids, 10%-20% EGCG, 1%-10% polyols, 10%-50% organic solvents, and 13%-78% water, and the total content of each component is 100%; In step (2), the mixed solution contains 0.3±0.2% phospholipid, 0.15±0.05% rigid membrane material stabilizer, 1.5%±0.5% flexible membrane material stabilizer, 5%-50% polyol, 1.0%-10% nanocomposite precursor, and 37.3%-88.4% water.

4. The preparation method according to claim 3, characterized in that: The phospholipid in step (1) is at least one of soybean lecithin, hydrogenated soybean lecithin, enzymatic lecithin, dipalmitoylphosphatidylcholine, palmitoylphosphatidylglycerol and egg yolk lecithin; The phospholipid in step (2) is at least one of soybean lecithin, hydrogenated soybean lecithin, dipalmitoylphosphatidylcholine, palmitoylphosphatidylglycerol and egg yolk lecithin.

5. The preparation method according to claim 4, characterized in that: The organic solvent in step (1) is one or more of anhydrous ethanol, methanol, dichloromethane, chloroform, acetone, tetrahydrofuran, n-hexane, petroleum ether, and ethyl acetate; The polyol in step (1) is a sugar alcohol, which is one or more of maltitol, D-sorbitol, xylitol, erythritol, mannitol, and lactitol; The polyol in step (2) is at least one of glycerol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,2-hexanediol, ethoxydiglycol, dipropylene glycol, and polyethylene glycol.

6. The preparation method according to claim 5, characterized in that: The stirring conditions for the first two times of step (1) are as follows: the stirring speed is 100-800 rpm; the stirring temperature is 30-80°C; the stirring time is 20-60 min; the dropping speed is 1-10 ml / min; the stirring conditions for the third time are as follows: the stirring speed is 100-800 rpm; the stirring temperature is 30-80°C; the stirring time is 10-30 min; the organic solvent is removed from the obtained mixed solution by rotary evaporation, the rotary evaporation speed is 100-350 rpm; the rotary evaporation temperature is 30-80°C; the rotary evaporation time is 1-3h; The stirring conditions for the first two times of step (2) are as follows: stirring speed of 100-800 rpm; stirring temperature of 10-50°C; stirring time of 20-60 min; and dropwise addition rate of 1-10 mL / min; the stirring conditions for the third time are as follows: stirring speed of 100-800 rpm; stirring temperature of 10-50°C; and stirring time of 10-30 min.

7. The preparation method according to claim 6, characterized in that: The rotation speed of the high-speed shear dispersion treatment in step (2) is 6000-12000 rpm, and the shear dispersion time is 10-30 min; the homogenization pressure of the microfluidization homogenization treatment is 50-120 MPa, and the number of homogenization cycles is 2-6 times.

8. The EGCG nanocomposite prepared by the method according to any one of claims 1 to 7.

9. Use of the EGCG nanocomposition according to claim 8 in preparing a skin external preparation.

Citation Information

Patent Citations

  • Anti-aging co-transport nanolipid vesicle and preparation method and application thereof

    CN109044921A

  • Antioxidant nano composition as well as preparation method and application thereof

    CN115844750A